Simultaneous Estimation of Metoprolol and Telmisartan in Combined Tablet Dosage Form by Using RP-HPLC and UV Spectrophotometry - Gandu, Sravanthi; ., Parameshwari; M, Ravinder; Gandla, Kumaraswamy; Narmada, Gade (Asian Journal of Pharmaceutical Research and Development, 2022)
An accurate, precise and reproducible RP-HPLC and UV Spectrophotometric method was developed and validated for the simultaneous estimation of Metoprolol and Telmisartan in tablet dosage form. The chromatographic separation was carried out on X-tera C8 column (100mm*4.6mm*5µ), by using the mobile phase (0.05M Sodium phosphate buffer pH 2.8 and methanol) in the ratio 35:65, at a flow rate 1.2ml/min. The detection was carried out at a wave length of 226nm. The retention time for Metoprolol and Telmisartan was found to be 2.338 and 5.559 respectively. UV method involves solving simultaneous equations based on measurement of absorbance at two wavelengths 223nm and 296nm λmax of Metoprolol and Telmisartan respectively. Beer’s law was obeyed in the concentration range of 1.25-6.25μg/ml and 2-10μg/ml for Metoprolol and Telmisartan respectively. The developed methods were validated according to ICH guidelines.